Mass Spectrometry of Atmospheric Pressure Surface Wave Discharges. (May 2016) - Ridenti, M A; Souza-Corrêa, J A; Amorim, J
Abstract: By applying mass spectrometry techniques, we carried out measurements of ionic mass spectrum and their energy distribution in order to investigate an atmospheric argon discharge by using a surfatron surface-wave device. The mass and energy distribution measurements were performed with fixed flow rate (2.5 SLM) of pure argon gas (99.999%) and different Ar-O2 gas mixture compositions (99-1, 98-2 and 97-3). The mass spectra and energy distributions were recorded for Ar +, O +, O + 2, N + and N2 + . The axial distribution profiles of ionic mass and their energy were obtained for different experimental conditions as a function of the plasma length. The results showed that the peak of the positive ion energy distributions shifted to higher energies and also that the distribution width increased as the distance between the sampling orifice and the launcher gap was increased. It was also found that under certain experimental conditions the ion flux of atomic species were higher than the ion flux of their diatomic counterpart. The motivation of this study was to obtain a better understanding of a surface wave discharge in atmospheric pressure that may play a key role on new second generation biofuel technologies.